¿Qué debe hacer un filósofo argentino? - Comesaña, Manuel (Revista de Filosofía, 2007)
The following theses are defended: 1) philosophical problems are universal; 2) it is not necessary, and it is probably not even convenient, that philosophy have “public intervention”; 3) when the philosopher talks about subject matters in which he is not a specialist the philosopher can offer no more than common-sense, in the best case a more or less reflective and enlightened common-sense; 4) Argentine philosophers almost never argue among them in print (they in general do it with philosophers of the First World who, with honorable exceptions, have never realized that they have been refuted in our country), but the idea that the cause of this situation is that Argentine philosophers do not work on topics that are of interest to their compatriots and that therefore the treatment for the illness must consist in their changing the topic is, to say the least, highly disputable; 5) everyone has the right to research whatever topic he wishes independently of the practical utility or “social impact” that the results of that research might have.